My three years in Manipur - Grimwood, Clair (New Delhi Gyan Publishing House, 2000)
Manipur lying between Cachar, the Kubo Valley and Nagaland is one of the most beautiful places in the world. Starting with an account of Grimwood's arrival in Manipur, the book goes on to describe Cachar and the hill tribes, Maos, Tongkhulls, Kukis etc. T
Keywords: Grimwood, Clair-Biography; Manipur-Description and travel